APLIKASI PENDAFTARAN PPDB (PENERIMAAN PESERTA DIDIK BARU) PROGRAM BABY SITTER BERBASIS WEB DI LEMBAGA KURSUS DAN PELATIHAN TIARA MEDICA CIAMIS DENGAN METODE AGILE - Aliffandi, Imam; Mulyana, Dadan; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
This study aims to develop an online registration system at LKP Tiara Medica Ciamis using the Agile SDLC method. The system is designed to replace the inefficient manual registration process with a more flexible and accessible online system. The development process included planning, design, development, and testing phases. The results show that the developed online registration system significantly improves registration efficiency, allowing prospective students to register from anywhere without needing to visit the location in person, and simplifying the administrative process. The system also includes online payment and data verification features, enhancing the accuracy and security of participant data. Recommendations include continuous testing and optimization, user training.